2022
DOI: 10.3390/atmos13020177
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial and Temporal Distribution Patterns of XCH4 in China: New Observations from TROPOMI

Abstract: Methane is the second most important greenhouse gas after carbon dioxide. The intensity and distribution of methane source/sink in China are unknown. We collected the column-averaged dry air mixing ratio of CH4 (abbreviated as XCH4 hereafter) from TROPOMI for the period from 2018 to 2021, to study spatial distribution and temporal change of atmospheric CH4 concentration, providing clues and foundations for understanding the source/sink in China. It was found that the distribution of XCH4 is roughly high in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A series of scientific works show that satellite monitoring is a powerful tool for measuring greenhouse gas emissions and concentrations. Mobile systems [55], CubeSats [56], and other satellites like the TROPOMI in China [57] can be used to make these measurements. Satellite monitoring can provide data on a global scale, which can be used to track changes in greenhouse gas emissions over time and to identify sources of emissions.…”
Section: Discussionmentioning
confidence: 99%
“…A series of scientific works show that satellite monitoring is a powerful tool for measuring greenhouse gas emissions and concentrations. Mobile systems [55], CubeSats [56], and other satellites like the TROPOMI in China [57] can be used to make these measurements. Satellite monitoring can provide data on a global scale, which can be used to track changes in greenhouse gas emissions over time and to identify sources of emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [35] carried out a study in different regions of China and found that, in the northern hemisphere, there is an increase in CH 4 in summer compared to winter.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%
“…However, the spatiotemporal variations of CH 4 emissions have not been well understood [6]. For instance, China is a major CH 4 emitter but has not yet compiled its own CH 4 emission inventory [7]. Satellite data are important for emissions, mainly through the top-down method, which is complementary to the bottom-up inventory.…”
Section: Introductionmentioning
confidence: 99%